Air Force Special Operations Command - Whiting, Jim, 1943- (Mankato, MN : Creative Education, 2014)
"A chronological account of the American special forces unit known as Air Force Special Ops, including key details about important figures, landmark missions, and controversies"--
Little-known yet much-appreciated -- Training to be the top -- Gear for getting the job done -- Memorable missions -- Glossary.
Includes bibliographical references and index.
Keywords: United States. -- Air Force -- Commando troops -- Juvenile literature; United States. -- Air Force Special Operations Command -- Juvenile literature; Special forces (Military science) -- United States -- Juvenile literature; Special operations (Military science) -- Juvenile literature